1991
DOI: 10.1007/bf00228666
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a mutation conferring high NaCl tolerance to gametophytes of Ceratopteris

Abstract: Spores from a weakly salt tolerant strain of Ceratopteris richardii containing the mutation stl1 were irradiated and sown on nutrient medium supplemented with 200 mM NaCl. A single highly salt tolerant gametophyte was recovered and selfed to generate a homozygous sporophyte. Spores from this strain, 10α23, were used to document the sexual transmission of the trait and to monitor the inheritance of tolerance in crosses to both the wild type and to the parental salt tolerant strain. Genetic analysis showed the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Precordate gametophytes from each strain were transferred to control medium (3.7 mM K+ ), to medium supplemented with 200 mM NaCl, and to medium without added K+, i.e., trace K+. All strains examined exhibit co-segregation of stl2-type salt tolerance (Hickok et al 1991) and K+ sensitivity (Vogelien et al 1995). These data along with the genetic origin of the mutation in a completely homozygous line and subsequent genetic analyses lend further support for a single gene basis for the salt-tolerant phenotype and corresponding ion transport phenomena.…”
Section: Responsesmentioning
confidence: 58%
See 4 more Smart Citations
“…Precordate gametophytes from each strain were transferred to control medium (3.7 mM K+ ), to medium supplemented with 200 mM NaCl, and to medium without added K+, i.e., trace K+. All strains examined exhibit co-segregation of stl2-type salt tolerance (Hickok et al 1991) and K+ sensitivity (Vogelien et al 1995). These data along with the genetic origin of the mutation in a completely homozygous line and subsequent genetic analyses lend further support for a single gene basis for the salt-tolerant phenotype and corresponding ion transport phenomena.…”
Section: Responsesmentioning
confidence: 58%
“…Segregation tests subsequently showed that 10a23 carried two unlinked mutations, stll and stl2 ( fig. 1; Hickok et al 1991). The new mutation, stl2, exhibited partial additivity with stll and independently conferred tolerance up to 275 mM NaCl.…”
Section: Ceratopteris and Salt-tolerant Mutantsmentioning
confidence: 97%
See 3 more Smart Citations